Pedagogical Content Knowledge (PCK) Analysis for Teachers: A Case Study of Pancasila and Citizenship Education (PPKn) Teachers on Bhinneka Tunggal Ika Material - Raya, Aqshal Arlian; Rima Vien Permata Hartanto; Rusnaini (HM Publisher, 2024)
Pancasila and citizenship education (PPKn) plays an important role in cultivating the values of Bhinneka Tunggal Ika in students. The PPKn teacher's ability to convey this material is very important. This research aims to analyze the pedagogical content knowledge (PCK) of PPKn teachers at SMA Negeri 5 Metro on Bhinneka Tunggal Ika material. This research uses a qualitative method with a case study of two class XII PPKn teachers. Data was collected through learning observations, interviews, and documentation studies. Data analysis was carried out using the Miles and Huberman technique. The research results showed that the first teacher showed PCK with good criteria in all components (teaching knowledge, student knowledge, and content knowledge). The second teacher showed PCK with fairly good criteria in all components. In general, both teachers have quite good PCK in teaching Bhinneka Tunggal Ika material. The first teacher showed better PCK than the second teacher.